Logistical Bottlenecks and Captured Value Chains: A Process Flow Analysis Of Small-Scale Salt Farmers In Jeneponto, Indonesia - Sitti Khadijah Yahya Hiola; Sitti Arwati; Amanda Patappari Firmansyah (Tarjih : Agribusiness Development Journal, 2026)
Jeneponto Regency is a salt-producing area in South Sulawesi with great potential for small-scale salt production growth. This study aims to trace the flow of small-scale salt products and reveal logistical barriers and relationships between actors in the supply chain. A qualitative approach was used through semi-structured interviews with 38 salt farmers, 3 traders, and 2 distributors. The results of the study show that the flow of small-scale salt from upstream to downstream is hampered by a long, fragmented, and unintegrated supply chain, which slows down distribution. The contribution of this study to critical logistics points is evident in the limited storage facilities and various logistical constraints that prevent the optimal implementation of post-harvest salt procedures, resulting in low-quality salt. The market structure also shows a pattern of a controlled value chain, where farmers are highly dependent on a single dominant actor, namely the collector trader, who controls the community's salt supply chain, forming a captured value chain pattern. This research provides scientific contributions through efforts to develop community salt logistics capable of improving salt quality, while also providing policy recommendations for the government through the strengthening of farmer institutions to reduce dependence on collectors and increase bargaining power in the value chain.